Effect of selected diets on the growth and survival of snakehead fish (channa striatus) fry. - Mohd Pazai, Afzan Muntaziana; Nurul Amin, Sanker Mohammad; Kamarudin, Mohd Salleh; Abd Rahim, Abdullah (Academic Journals, 2013)
Twenty-five days feeding trial was conducted to evaluate the growth and survival of Channa striatus fry fed with three types of fresh foods (bloodworm, trash fish and Acetes shrimps). Ten fry were stocked in each aquarium (46x46x37 cm) and fed ad libitum twice a day (1000 and 1700 h). All treatments were triplicate. The fry fed trash fish showed a significantly (p<0.05) higher weight gain percentage (376.50±20.74%) than those fed with Acetes shrimp (233.05±10.18%) and bloodworm (199.08±17.25%). The final mean total lengths of fry fed with trash fish, bloodworm and Acetes shrimps were 7.91±0.23, 7.28±0.23 and 7.21±0.17 cm, respectively. Fry fed with trash fish also showed the best Specific Growth Rate (SGR) value (6.24±0.17% day-1) followed by Acetes shrimp (4.81±0.12% day-1) and bloodworm (4.33±0.22% day-1). The best Food Conversion Ratio (FCR) value (3.63±0.27) was found among fish fed with trash fish compared to those fed Acetes shrimp (7.41±0.88) and bloodworm (11.48±1.51). It could be concluded that trash fish was an excellent feed for C. striatus fry in term of growth, weight gain and FCR.